Vocabulary Learning Strategies Used by Learners of Arabic as a Foreign Language in the University of Islamic Sciences in Malaysia and their Beliefs about Vocabulary Learning - Alhashemi, Abdullah; Ali, Mahmoud (Jordan Journal of Educational Sciences, 2012)
This study investigates the vocabulary learning strategies of undergraduate Malaysian learners of Arabic as a foreign language (AFL) in terms of frequency of use and beliefs. A total of 67 first year learners of Arabic in the University of Islamic Sciences responded to a questionnaire composed of two main themes– strategies (45 items) and beliefs (20 items). The findings revealed that Malaysian AFL learners use vocabulary learning strategies at approximately the same level of frequency. However, it was found that dictionary related strategies were used more frequently in contrast to other strategies, namely, note taking, memorization, and guessing, which was the least usually used strategy. Furthermore, Malaysian AFL learners generally agree on the importance of using different approaches in manipulating and learning Arabic vocabulary.